Passively mode-locked diode-pumped Tm3+:YLF laser emitting at 1.91 µm using a GaAs-based SESAM. (9th March 2018) - Tyazhev, A; Soulard, R; Godin, T; Paris, M; Brasse, G; Doualan, J-L; Braud, A; Moncorgé, R; Laroche, M; Camy, P; Hideur, A
Abstract: We report on a diode-pumped Tm:YLF laser passively mode-locked with an InGaAs saturable absorber. The laser emits a train of 31 ps pulses at a wavelength of 1.91 µ m with a repetition rate of 94 MHz and a maximum average power of 95 mW. A sustained and robust mode-locking with a signal-to-noise ratio of 70 dB is obtained even at high relative air humidity, making this system attractive for applications requiring ultra-short pulses in the spectral window just below 2 µ m.